Síntese e caracterização de heteroestruturas de quitosana/ G-C3n4 para fotodegradação de micropoluentes - Rodríguez-Pérez, Adriana Patricia (2021)
Due to the limitation of conventional treatment processes, some contaminants are not efficiently removed, in this context, heterogeneous photocatalysis appears as an alternative for contaminant degradation. Recently, graphitic carbon nitride (g-C3N4) has attracted attention as a metal-free catalyst due to its characteristics of electronic conductivity, visible light absorption, and low cost. In this work, the synthesis of photocatalysts was proposed: g-C3N4 from urea (U) or melamine (M), called g-C3N4/U and g-C3N4/M via carbonization; and spherical heterostructures of chitosan (Q) with urea (U) or melamine (M), called: Q:U and Q:M in different proportions. The materials were characterized by: X-ray diffraction, with characteristic peaks at 12.92° (1 0 0) and 27.58° (0 0 2) , corresponding to the formation of g-C3N4, in addition to microcrystallinities associated with the chitosan (20°); diffuse reflectance spectroscopy, , determining band gap values around 3.15 eV; X-ray photoelectron spectroscopy, having the binding energies associated with the intermediate (melem) of g-C3N4/U also confirmed also with the data of the C/N radio in the CHN analysis, FTIR showing the functional groups of the tri-s-triazines (structural units of g-C3N4) and finally by scanning electron microscopy, morphological images of the material were taken before and after photodegradations, where morphological images of the material were obtained before and after photodegradations, observing that the chitosan spheres did not show wear. In the photocatalytic studies, the removal of model pollutant – Rhodamine B (RhB) dye was evaluated with all synthesized materials; in the desethyl-atrazine (DEA) and Rifampicin (RIF) was used the materials that showed better removal of the model pollutant; in addition to the evaluation of physicochemical parameters using g-C3N4/U and g-C3N4/M before (pre-treatment) and after (post-treatment) of biological treatment, using an anaerobic upflow reactor and sludge blanket (UASB type) in a hospital wastewater. Different configurations were used for each degradation: type of radiation (UVA-Vis, Vis) / lamp (high pressure of mercury vapor, LED, Halogen) configurations were used with ad without the use of filter (f) cut at λ > 420 nm, in addition to using a suspended lamp (S) at 10 cm from the solution or submerged lamp (M). Preliminary results in the UVAM region were obtained with dye degradation of up to 99.9%. In the Vis LEDS region, there was an increase of 9.3% of g-C3N4/M up to 15.2% with chitosan (3Q:1M), showing that recombination problems are improved by mixing the photocatalyst with the carbon matrix (chitosan) as well as being easily separated from the solution and reused. In the removal of DEA and RIF, in all configurations, higher removal efficiencies were obtained with the heterostructures (3Q:1U, 3Q:1M) compared to pure g-C3N4, obtaining degradations in up to 30-45 minutes in some cases. The raw hospital effluent, after the anaerobic biological treatment by a UASB reactor, obtained a considerable decrease in COD and BOD5, thus establishing a degradation of almost 87% of the organic matter. In the combined process, COD removal efficiencies of 84.7% for g-C3N4/U and 77% for g-C3N4/M were obtained. Thus, materials based on g-C3N4 constitute an alternative for use in photocatalytic processes.